2012
DOI: 10.1007/s12471-012-0302-x
|View full text |Cite
|
Sign up to set email alerts
|

Six-month clinical outcomes of the Tryton Side Branch Stent for the treatment of bifurcation lesions

Abstract: Aims Percutaneous coronary intervention (PCI) of a bifurcation lesion (BL) is still associated with poorer clinical outcomes when compared with PCI of a non-BL. Therefore, several dedicated coronary bifurcation stents, such as the Tryton Side Branch Stent™ (Tryton Medical, Durham, NC, USA), were developed to improve clinical outcomes. We investigated 6-month clinical outcomes after placement of a Tryton stent in 91 patients treated for 93 BLs in our centre. Methods and results All consecutive patients who have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…Previous observational studies on the Tryton stent consistently showed six‐ to twelve‐month TLR rates of ∼4% . The current report showed that these results are sustainable up to two years of follow‐up, TLR rate increased from 5.8% at one‐year up to 9.2% at two years.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…Previous observational studies on the Tryton stent consistently showed six‐ to twelve‐month TLR rates of ∼4% . The current report showed that these results are sustainable up to two years of follow‐up, TLR rate increased from 5.8% at one‐year up to 9.2% at two years.…”
Section: Discussionsupporting
confidence: 68%
“…Clinical outcomes were reported as cardiac death, any myocardial infarction (MI), target vessel revascularization (TVR), target lesion revascularization (TLR), definite or probable stent thrombosis (ST), and target vessel failure (TVF), defined as the composite of cardiac death, any MI, and TVR. All outcome definitions were similar to our previous publication , except that for the current analysis, TLR was further stratified to TLR of the MB and/or TLR of the SB.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To improve clinical outcomes after PCI of coronary bifurcation lesions, several dedicated bifurcation devices, such as the Tryton Side-Branch Stent TM (Tryton Medical, Durham, NC), have been developed. Previous smaller registry studies [10][11][12][13] and a patient pooled analysis [14] with this stent in de novo bifurcation lesions showed promising procedural and clinical outcomes. Tryton is a side branch first bare-metal stent and its specific design, with a minimal amount of metal in the proximal main branch zone, facilitates easy delivery of a regular drug-eluting stent (DES) in the main branch [15].…”
Section: Introductionmentioning
confidence: 99%